Compliance with maternal HIV retesting for pregnant women attending care in selected health facilities in Namutumba district, Uganda - Shafik Malende; Edward Buzigi; Esther Bayiga (BMC Health Services Research)
Abstract Background Retesting for HIV during pregnancy, labor, and postpartum is crucial for identifying new infections and ensuring timely interventions to prevent mother-to-child transmission (PMTCT). Uganda's national guidelines recommend that pregnant women be retested in the 3rd trimester or during labor/delivery. However, limited information exists regarding adherence to these guidelines, which may affect the effectiveness of PMTCT efforts. Aim To assess compliance with maternal HIV retesting and the factors influencing retesting among pregnant women attending care in selected health facilities in Namutumba district. Methods This cross-sectional study was conducted from January to June 2024 in six government health facilities in Namutumba district. Quantitative data were collected from randomly selected mothers who delivered during the study period using a structured questionnaire in an open data kit. For the qualitative component, data were collected through key informant interviews with healthcare workers to explore barriers and facilitators to HIV retesting. Quantitative data were analyzed using STATA version 17, while qualitative data underwent manual thematic analysis. Results The study showed that most respondents were young women, with an average age of 25.7 years, most of whom lived in rural areas (89.3%) and were married (88%). HIV retesting prevalence was 85%. Key factors associated with retesting included secondary education [APR 1.55, 95% CI (1.03-2.34)], tertiary education [APR 1.72, 95% CI (1.10-2.61)], attending at least five ANC visits [APR 1.11, 95% CI (1.01-1.21)], and spousal accompaniment for ANC or delivery [APR 1.18 (1.05-1.34)]. Facilitators included community outreach, education, and incentives while barriers involved testing kit shortages, poor documentation, stigma, and human resource constraints. Conclusions HIV retesting in Namutumba district's high-volume health facilities was below the recommended 100% needed to eliminate mother-to-child transmission. Recommendations Prioritize interventions to increase retesting uptake, focus on health education, promote spousal involvement, and address human resource gaps in HIV testing services.